Faktor yang Mempengaruhi Kinerja Pegawai di Dinas LH dan Kehutanan Kepulauan Riau - Sukardi , Sukardi; Indrawan, M. Gita; Friadi, John; Satriawan, Bambang; Wibisono, Chablullah; Yasa, I Wayan Catra (Penerbit Goodwood, 2025)
Purpose: This study aims to analyse the factors that influence performance through employee job satisfaction at the Environmental and Forestry Service of the Riau Islands Province. Methodology/approach: The research methodology uses a quantitative method with a population and sample of 131 respondents, namely employees of the Environmental and Forestry Service of the Riau Islands Province. Data analysis uses SEM PLS 3.0. Results/findings: Leadership (X1) on Employee Performance (Y) through Job Satisfaction (Z) has a positive and significant effect with a P value of 0.008, Motivation (X2) on Employee Performance (Y) through Job Satisfaction (Z) has a positive but insignificant effect with a P value of 0.053, Discipline (X3) on Employee Performance (Y) through Job Satisfaction (Z) has a positive but insignificant effect with a P value of 0.169. Conclusions: Based on the results of the analysis and discussion of the research that has been presented, it can be concluded as follows that leadership has a positive and insignificant influence on employee performance. Limitations: The Environment and Forestry Service of Riau Islands Province needs to continue to improve employee performance, especially employee motivation by giving awards to high-achieving employees, involving employees in training and technical guidance, and assessing employee performance objectively. In addition, leadership style, discipline, and job satisfaction need to be optimized to improve performance. Contribution: This study contributes to analysing the factors that influence employee performance improvement at the Environmental and Forestry Service of the Riau Islands Province through leadership, motivation, discipline and job satisfaction.